A Dialogical, Multi‐Agent Account of the Normativity of Logic. (December 2015) - Dutilh Novaes, Catarina
Abstract: The paper argues that much of the difficulty with making progress on the issue of the normativity of logic for thought, as discussed in the literature, stems from a misapprehension of what logic is normative for . The claim is that, rather than mono‐agent mental processes, (deductive) logic in fact comprises norms for quite specific situations of multi‐agent dialogical interactions, in particular special forms of debates. This reconceptualization is inspired by historical developments in logic and mathematics (briefly surveyed in the paper), in particular the pervasiveness of such dialogical conceptions in the early days of logic in ancient Greece. The multi‐agent, dialogical perspective then allows for the formulation of compelling 'bridge principles' between the relation of logical consequence and dialogical normative principles, something that is notoriously difficult to achieve in a mono‐agent setting pertaining exclusively to thought and belief. The upshot is also that the truth‐preserving rules of logic generally do not have a primary normative bearing on mono‐agent mental processes, and in this sense the paper sides with Harman's (1986; 2009) critique of the idea that logic has a normative import for thought and belief.